Policy Updates In Efforts To Prevent And Handle Criminal Acts Of Human Trafficking To Increase Protection For Women And Children From Exploitation - Ahmad Haikal; Evita Isretno Israhadi (Jurnal Multidisiplin Indonesia, 2025)
Human Trafficking (TPPO) is a transnational crime that is increasingly worrying, especially because women and children are the groups most vulnerable to exploitation. Gender-based TPPO often involves sexual exploitation, forced labor, and modern slavery, which are influenced by economic, and social factors, and weaknesses in the legal system. Gender discrimination, poverty, and unequal access to education and employment are the main factors that push women and children into human trafficking networks. In addition, patriarchal culture and social norms that place women in subordinate positions further exacerbate their vulnerability to exploitation. This study aims to analyze patterns of exploitation of women and children in TPPO and identify the main causal factors that contribute to the high number of victims from this group. This study uses a qualitative method with a descriptive-analytical approach. The data used comes from secondary sources, such as official reports from international organizations (ILO, UNODC, UNICEF), academic journals, and national policies related to TPPO. Data analysis was carried out using a thematic approach to identify patterns of gender-based exploitation, main causal factors, and policy responses that have been implemented by various parties in dealing with and preventing human trafficking. This study also refers to feminist theory to understand how social structures and gender norms contribute to the vulnerability of women and children in cases of TPPO. By understanding the dynamics of this exploitation, it is expected that this study can provide more effective recommendations in efforts to prevent and protect victims of TPPO, as well as encourage policies that are more inclusive and responsive to gender issues.